Immune Checkpoint Inhibitor-Related Sjögren’s Syndrome: An Ocular Immune-Related Adverse Event - Hideki Fukuoka; Akifumi Matsumoto; Chie Sotozono (Diagnostics)
A 67-year-old male with metastatic human papillomavirus (HPV)-positive oropharyngeal cancer receiving pembrolizumab (anti-programmed cell death protein 1 [PD-1] immune checkpoint inhibitor) presented with bilateral ocular dryness. It is important to note that these symptoms appeared eight months after the initiation of the pembrolizumab therapy. Ophthalmologic evaluation revealed keratoconjunctivitis sicca with characteristic bulbar fluorescein staining and the Schirmer test showed 0 mm bilaterally. Serological testing demonstrated positive antinuclear and anti-SSb/La antibodies, consistent with Sjögren’s syndrome as an immune-related adverse event (irAE). Treatment with topical fluorometholone 0.1% and diquafosol 3% led to complete symptom resolution within one year while maintaining cancer immunotherapy. Long-term follow-up over 3.5 years demonstrated sustained ocular improvement and a favorable oncologic response without development of systemic autoimmune manifestations. This case highlights that Sjögren’s syndrome as an irAE may present with isolated ocular manifestations, which could be overlooked in clinical practice.